2008
DOI: 10.1021/bp070359s
|View full text |Cite
|
Sign up to set email alerts
|

A Microscale Yeast Cell Disruption Technique for Integrated Process Development Strategies

Abstract: Miniaturizing protein purification processes at the microliter scale (microscale) holds the promise of accelerating process development by enabling multi-parallel experimentation and automation. For intracellular proteins expressed in yeast, small-scale cell breakage methods capable of disrupting the rigid cell wall are needed that can match the protein release and contaminant profile of full-scale methods like homogenization, thereby enabling representative studies of subsequent downstream operations to be pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…Several extraction techniques are there to recover the potent BG from microbial and plant sources, but the choice of suitable extraction method plays a vital role that will affect the structure, quality, and functionality of the BG (Ahmad et al, 2012 from cytoplasm) and BG extraction (extraction from insoluble cell wall) (Javmen et al, 2012). Several studies reported about chemical (NaDH, HCl, acetic acid, citric acid) (Lee et al, 2001;Hunter et al, 2002;Pelizon et al, 2005), physical (sonication, high pressure) (Boonraeng et al, 2000;Shokri et al, 2008;Wenger et al, 2008) and enzymatic (lytic enzymes) lysis of yeast cells (Ferrer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several extraction techniques are there to recover the potent BG from microbial and plant sources, but the choice of suitable extraction method plays a vital role that will affect the structure, quality, and functionality of the BG (Ahmad et al, 2012 from cytoplasm) and BG extraction (extraction from insoluble cell wall) (Javmen et al, 2012). Several studies reported about chemical (NaDH, HCl, acetic acid, citric acid) (Lee et al, 2001;Hunter et al, 2002;Pelizon et al, 2005), physical (sonication, high pressure) (Boonraeng et al, 2000;Shokri et al, 2008;Wenger et al, 2008) and enzymatic (lytic enzymes) lysis of yeast cells (Ferrer, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Results of the studies by authors of [22,23] (on the ability of alkali-silicate systems with Al 2 O 3 to form insoluble products of Na 2 O·Al 2 O 3 ·2Si 2 O 3 ·nH 2 O in alkaline media) specify aluminum oxide of ash as a modifying component. It provides raw mixture with qualities required for the targeted product creation.…”
Section: Discussion Of Results Of Research Into the Processes Of Bloamentioning
confidence: 99%
“…We p F R W (13) As is known, the capillary force F σ regardless the shape of the deformed droplet always restores the spherical shape and the minimum Gibbs surface energy (steady state) is reached. Therefore, if the drop is deformed in the direction of its motion to a flattened ellipsoid, the capillary force counteracts the external force.…”
mentioning
confidence: 90%
“…For example, in a water-oil type emulsion, interfacial tension is σ wo ≈16 mN/m, and tension at the water-vapor interface σ wv ≈73 mN/m [13]. At the same time, tension at the water-vapor interface with microscopic oil additives decreases to a value of σ wv ≈39...41 mN/m.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%